Eksternalitas Kegiatan Industri Terhadap Kinerja Jalan (Studi Kasus: Jalan Sadang - Batas Purwakarta / Subang) - Sukandar, Edi; Wijaya, Holi Bina (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2015)
Increased industrial activities in Sadang road – Purwakarta/Subang Boundaries cannot be separated from the increasing accessibility and local government policies related to the location of industrial allotment. On one hand, industrial activities have increased the region's economy, but on the other hand they have caused negative externalities in the form of traffic congestion as a result of the increasing volume of vehicles during peak hours. Socio-economic impacts felt by road users in the event of congestion are clearly visible from the lost benefits and costs incurred. The congestion cost is an addition to travel cost borne by road users due to increasing traffic volume and travel time. This research aims to determine the contributions of the movement of people and goods produced by industrial activities as well as the loss value incurring due to the presence of externalities of industrial activities on the road performance. This study used quantitative method with the analysis of congestion cost as the approach of loss value of road users. The analysis of congestion costs were based on vehicle operating costs (VOC), traffic flow, vehicle speed, travel time value and the amount of queue time.